1996
DOI: 10.1093/cercor/6.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Functional Topography: Multidimensional Scaling and Functional Connectivity in the Brain

Abstract: In neuroimaging, functional mapping usually implies mapping function into an anatomical space, for example, using statistical parametric mapping to identify activation foci, or the characterization of distributed changes with spatial modes (eigenimages or principal components) (Friston et al., 1993a). This article is about a complementary approach, namely, mapping anatomy into a functional space. We describe a simple variant of multidimensional scaling (principal coordinates analysis; Gower, 1966) that uses fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
159
1
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(165 citation statements)
references
References 25 publications
(29 reference statements)
0
159
1
5
Order By: Relevance
“…In a PET study of verbal fluency, Friston et al (1996) found an abnormal positive correlation between left STG and left DLPFC in schizophrenia, as did Fletcher et al (1999) using a verbal memory task. Jennings et al (1998) used structural equation modeling in a PET study of semantic categorization and found that the influence of left ventral PFC (BA 45) on left STG activity was positive in controls but negative in patients, in the context of equal task-related prefrontal and temporal activation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a PET study of verbal fluency, Friston et al (1996) found an abnormal positive correlation between left STG and left DLPFC in schizophrenia, as did Fletcher et al (1999) using a verbal memory task. Jennings et al (1998) used structural equation modeling in a PET study of semantic categorization and found that the influence of left ventral PFC (BA 45) on left STG activity was positive in controls but negative in patients, in the context of equal task-related prefrontal and temporal activation.…”
Section: Discussionmentioning
confidence: 93%
“…In a related series of PET studies Fletcher et al, 1996;Friston et al, 1996;Fletcher et al, 1999), healthy controls performing verbal tasks activated prefrontal regions (left DLPFC, anterior cingulate) and deactivated superior temporal gyrus (STG). In contrast, schizophrenia patients showed less STG deactivation (relative overactivation) and a positive prefrontal-STG correlation.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of this integrative view of executive functioning will require statistical methods devoted to explore correlations between remote neurophysiological events ("functional connectivity") as well as the influence that one neuronal system exerts over another. ("effective connectivity") [49,50] In conclusion, functional neuroimaging studies have contributed considerably to a better understanding of the central executive of working memory or executive functioning. Indeed, studies using these techniques have clearly demonstrated that executive functioning requires both prefrontal and parietal regions.…”
Section: Discussionmentioning
confidence: 99%
“…This data-driven analysis allows the identification of interregional correlations (with consistent regression coefficients across subjects) in low-frequency (<0.1 Hz) spontaneous BOLD fluctuations in the brain which cannot be attributed to the experimental paradigm (Arfanakis et al, 2000;Biswal et al, 1995;Cordes et al, 2000;Fox and Raichle, 2007;Friston, 1995;Horwitz et al, 1992;Lowe et al, 1998;Xiong et al, 1999). Since this technique involves correlating signal changes in a seed region with signal changes in other parts of the brain, it can reveal functional interactions between brain areas (Friston et al, 1996). The fact that fcMRI is data-driven also means that it is task-driven rather than event-driven.…”
Section: Accepted Manuscriptmentioning
confidence: 99%